Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00198-008-0825-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term strontium ranelate treatment on vertebral fracture risk in postmenopausal women with osteoporosis

Abstract: Summary Vertebral fractures are a major adverse consequence of osteoporosis. In a large placebo-controlled trial in postmenopausal women with osteoporosis, strontium ranelate reduced vertebral fracture risk by 33% over 4 years, confirming the role of strontium ranelate as an effective long-term treatment in osteoporosis. Introduction Osteoporotic vertebral fractures are associated with increased mortality, morbidity, and loss of quality-oflife (QoL). Strontium ranelate (2 g/day) was shown to Osteoporos Int (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 42 publications
4
108
0
2
Order By: Relevance
“…In addition, in patients above the age of 74 years, the incidence of nonvertebral fractures was 16% lower in the strontium ranelate-treated group compared with the placebo group, and the risk of hip fractures diminished by 36% (Tournis et al, 2006). Furthermore, recent long-term studies (8 and 5 years) have reported a continued increase in bone mass density in strontium ranelate treated postmenopausal women and a reduced risk of fractures (Meunier et al, 2009;Reginster et al, 2009). …”
Section: ؉mentioning
confidence: 94%
“…In addition, in patients above the age of 74 years, the incidence of nonvertebral fractures was 16% lower in the strontium ranelate-treated group compared with the placebo group, and the risk of hip fractures diminished by 36% (Tournis et al, 2006). Furthermore, recent long-term studies (8 and 5 years) have reported a continued increase in bone mass density in strontium ranelate treated postmenopausal women and a reduced risk of fractures (Meunier et al, 2009;Reginster et al, 2009). …”
Section: ؉mentioning
confidence: 94%
“…Strontium ranelate is a treatment for osteoporosis that decreases the incidence of vertebral and femoral fracture risk in postmenopausal women (1)(2)(3). Strontium ranelate has been shown to modulate the physiological processes of bone formation and bone resorption (2), resulting in increased bone apposition rates (3) and bone mineral density (1, 2, 4 -6), while maintaining the quality of bone mineral (6).…”
mentioning
confidence: 99%
“…6 Awareness of the biological role of strontium has increased in recent years. 11,12 Physiological bone regeneration, a coordinated process, is maintained by boneforming osteoblasts and bone-resorbing osteoclasts. The 2 factors produced by osteoblasts forming the bone: receptor activator NF-κB ligand (RANKL) and osteoprotegerin (OPG) control the activity and differentiation of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%